Bifunctional plasmonic metamaterial absorber for narrowband sensing detection and broadband optical absorption. (May 2021) - Gao, Huixuan; Liang, Yuzhang; Yu, Li; Chu, Shuwen; Cai, Lina; Wang, Fei; Wang, Qiao; Peng, Wei
Highlights: Both narrowband and broadband absorbers are achieved on the single structure. Narrowband absorber is designed for high-sensitivity sensing detection. Broadband absorbers can be applied for efficient capturing solar energy. Abstract: Plasmonic perfect absorbers have attracted extensive attentions for their tremendous application potentials in the fields of sensing detection, harvesting solar energy, and saltwater purification. In this paper, we demonstrate a bifunctional plasmonic metamaterial absorber (BPMA), consisting of a multilayer planar architecture with etched upper surface, which exhibits distinguishing functions on both top and bottom sides. The dark flat bottom side of the BPMA can provide broadband perfect absorption for efficient capturing solar energy, while its metamaterial-based top side can achieve narrowband perfect absorption for high-sensitivity sensing detection. Finely optimizing the planar film thickness, the dark bottom side can achieve an average light absorption up to 84.09% from visible to near-infrared region under normal irradiance, which can stem from the high extinction coefficient of titanium inside multilayered waveguides and anti-reflection coatings effect. In addition, originating from surface plasmon polaritons Bloch mode, the narrowband absorption on the upper side exhibits narrow line width spectral fractures with high peak-to-dip signal ration, making it an ideal platform for high-sensitivity detection. The demonstration of this bifunctional perfect absorber on a single substrate provides a potential solution for multifunction photonic integration.